Evaluation of Physicians' Cognitive Styles. (July 2014) - Djulbegovic, Benjamin; Beckstead, Jason W.; Elqayam, Shira; Reljic, Tea; Hozo, Iztok; Kumar, Ambuj; Cannon-Bowers, Janis; Taylor, Stephanie; Tsalatsanis, Athanasios; Turner, Brandon; Paidas, Charles
Background. Patient outcomes critically depend on accuracy of physicians' judgment, yet little is known about individual differences in cognitive styles that underlie physicians' judgments. The objective of this study was to assess physicians' individual differences in cognitive styles relative to age, experience, and degree and type of training.Methods. Physicians at different levels of training and career completed a web-based survey of 6 scales measuring individual differences in cognitive styles (maximizing v. satisficing, analytical v. intuitive reasoning, need for cognition, intolerance toward ambiguity, objectivism, and cognitive reflection). We measured psychometric properties (Cronbach's α) of scales; relationship of age, experience, degree, and type of training; responses to scales; and accuracy on conditional inference task.Results. The study included 165 trainees and 56 attending physicians (median age 31 years; range 25–69 years). All 6 constructs showed acceptable psychometric properties. Surprisingly, we found significant negative correlation between age and satisficing ( r = −0.239; P = 0.017). Maximizing (willingness to engage in alternative search strategy) also decreased with age ( r = −0.220; P = 0.047). Number of incorrect inferences negatively correlated with satisficing ( r = −0.246; P = 0.014). Disposition to suppress intuitive responses was associated with correct responses on 3 of 4 inferential tasks. Trainees showed a tendency to engage in analytical thinking ( r = 0.265; P = 0.025), while attendings displayed inclination toward intuitive-experiential thinking ( r = 0.427; P = 0.046). However, trainees performed worse on conditional inference task.Conclusion. Physicians capable of suppressing an immediate intuitive response to questions and those scoring higher on rational thinking made fewer inferential mistakes. We found a negative correlation between age and maximizing: Physicians who were more advanced in their careers were less willing to spend time and effort in an exhaustive search for solutions. However, they appeared to have maintained their "mindware" for effective problem solving.